Pemanfaatan Sampah Organik Menjadi Pupuk Kompos oleh KKN Kelompok 28 di Desa Bantarsari - Muhamad Rizky Kurniawan; Aning Anugrah Widhi; Prisna Haula Primair; Asep Hidaya; Desti Fitri Ayu; Alda Alvita Fortuna; Anang Muhari; Agus Abdul Mutolib; 8Hamzah Nur Holis; Tini Martini (BADAN PENERBIT STIEPARI PRESS, 2025)
Organic waste is one of the major contributors to environmental problems in rural areas, particularly when it is not properly managed. Bantarsari Village, located in a rural setting, has a high potential for organic materials, yet most of these resources remain underutilized. The Community Service Program (KKN) Group 28 of Universitas Subang aimed to address this issue by introducing a sustainable waste management solution—turning household organic waste into compost. This initiative was designed to reduce environmental impact, promote eco-friendly practices, and foster community engagement. The study employed a descriptive qualitative method with field observation techniques to evaluate each stage of the program. These stages included community socialization, collection of organic materials such as food scraps and dry leaves, composting using EM4 activators, and monitoring the composting process until it was ready for use. The findings revealed that compost could be produced within 3 to 4 weeks, with numerous benefits, including improved soil fertility, reduced reliance on chemical fertilizers, a decrease in the volume of household organic waste, and the creation of economic opportunities through compost utilization and sales. Additionally, the program raised awareness in the community about the importance of independent, sustainable organic waste management practices. The collaboration between students and the local community proved successful in developing a simple, innovative solution that provided ecological, economic, and social benefits for rural areas